PREVENTION OF SUPERIMPOSED PREECLAMPSIA WITH LOW-DOSE ASPIRIN : A SYSTEMATIC REVIEW - Azkiya, Mayla (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Aspirin is currently the most widely prescribed treatment in the prevention of cardiovascular complications. At low doses, aspirin is also widely used to prevent pregnancy-related vascular disorders, such as preeclampsia and intrauterine growth restriction, and maternal disorders like antiphospholipid syndrome. The indications for the use of aspirin during pregnancy are, however, the subject of much controversy. The aim: This study aims to show prevention of superimposed preeclampsia with low-dose aspirin. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 39 articles, whereas the results of our search on SagePub brought up 106 articles. The results of the search conducted for the last year of 2013 yielded a total 25 articles for PubMed and 50 articles for SagePub. The result from title screening, a total 10 articles for PubMed and 22 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Aspirin initiated at or before 16 weeks of gestation is associated with a greater reduction in the incidence of PE, perinatal death, and other adverse perinatal outcomes as compared to aspirin initiated after 16 weeks of gestation.